(untitled) (Social and Environmental Law Journal, 2025)
The present study deals with the Legal Regime for the Expulsion of Foreigners in Mozambique, a very current topic, especially the expulsion of foreigners, as the coercive removal of individuals from territories outside their jurisdiction, observing all legal procedures for staying or leaving for reasons duly substantiated by the authorities with powers to carry it out. However, in Mozambican jurisdiction, it is incumbent upon the Minister who oversees the area of migration, specifically that of the Interior, on behalf of the Government to order the administrative expulsion, pursuant to paragraph 1 of article 40 of Decree No. 108/2014, of 31 December, which approves the regulation of Law No. 23/2022 of 29 December, the legal regime for Foreign Citizens and establishes the respective rules for entering, staying and leaving the country, as well as their rights, duties and guarantees and establishes the respective norms for entering, staying and leaving the country. Furthermore, in the Mozambican legal order, there are two types of expulsions, namely: administrative and judicial expulsion. Under the terms of number 2 of article 40 of Decree number 108/2014, of December 31, the foreign citizen covered by the administrative expulsion measure, if he so wishes, may file an appeal with the Administrative Court, without suspensive effects, in order to safeguard its permanence.